Aspiration Pneumonitis in an Obese Patient under General Anaesthesia for Fracture Humerus: A Case Report - Manoj Kumari Katewa; Rashmi Rashmi; Arvind Kumar; Manisha Kumari (Archives of Anesthesia and Critical Care)
Aspiration under general anaesthesia is a dreaded complication which can significantly affects the morbidity and mortility in the postoperative period. Factors such as delayed gastric emptying seen in obesity, pregnancy, paralytic ileus, altered consciousness as under general anaesthesia, head injury can predispose the patient to pulmonary aspiration. The two entities aspiration pneumonia and aspiration pneumonitis although difficult to differentiate in the early course of event but it is of crucial importance to know the pulmonary pathology for effective management of the patient. A morbidly obese patient was posted for fracture humerus surgery under GA who landed in cannot ventilate situation, had pulmonary aspiration which was managed efficiently in ICU.